Análise da aplicabilidade do EVA® em empresas de saneamento básico: estudo de caso da SABESP - Silva, Pamela Lima Felix da (2025)
SABESP, one of the largest basic sanitation companies in the world, has played a fundamental role in expanding water and sewage infrastructure in the state of São Paulo. With the recent privatization, this research evaluates whether the company, under public management, has generated economic value for its shareholders, using EVA® (Economic Value Added) as the main performance indicator. EVA® measures a company's ability to create wealth by comparing the returns generated with the cost of invested capital. The objective of this study is to analyze the economic value created by SABESPand to complement this analysis with the evaluation of financial indicators over the period from 2018 to 2024. The research uses a temporal analysis methodology to verify whether the company has maintained its ability to generate value and whether this trend can be sustained under future private management. The main contribution of this study is to provide a comprehensive analysis of the applicability of EVA® in a large public company listed on B3 that has recently been privatized (SABESP). Additionally, the work offers a foundation for future research that may investigate the transition from public to private management in the basic sanitation sector, with a focus on creating economic value for shareholder